Effect of combining exogenous fibrolytics enzymes with Saccharomyces cerevisiae or Eucalyptus essential oil on the in vitro ruminal fermentation and digestibility of wheat straw - JABRI, JIHENE; ABID, KHALIL; YAICH, HELA; MALEK, ATEF; REKHIS, JAMEL; KAMOUN, MOHAMED (The Indian Journal of Animal Sciences, 2019)
This study aimed to determine the efficacy of exogenous fibrolytics enzymes (EFE) to create a synergy with Saccharomyces cerevisiae (SC) or essential oil (Eucalyptus globulus) (EO) to promote the in vitro ruminal fermentation and digestibility of wheat straw (WS). The EFE was a mixture (1:1, v/v) of Î²-1, 3-1, 4-glucanase and endo-1,4-Î²-D-xylanase produced by the Trichoderma longibrachiatum. The WS was supplemented with EFE (EFE1=1, EFE2=2 Î¼l/g DM), SC (SC1=0.5, SC2=1 mg/g DM), EO (EO1=30, EO2=60 Î¼l/g DM) and the combinations EFE1+EO1, EFE1+EO2, EFE2+EO1, EFE2+EO2 and EFE1+SC1, EFE1+SC2, EFE2+SC1, EFE2+SC2. Compared to the control, both EFE and SC alone or in combination, improved the rate and the extent of WS fermentation. The potential GP improved only with EFE2, SC1, and EFE2+SC2 by 31.7, 24.9, 37.4% and the rate Rmax by 36, 59.2 and 55.2%, respectively. The organic matter digestibility and the energetic use of WS improved with the highest doses EFE2 and EFE2+SC2. While the EO alone or combined with the EFE had a depressive effect on all fermentation and digestibility parameters. The EFE seems to be more beneficial for the fermentation and digestibility of WS than when it was combined with SC or EO. Therefore, there is no synergetic effect between EFE and SC or EO with the used doses on fibrous by-product like wheat straw.